Targeting the cholinergic system in Parkinson’s disease - Liu Changliang (Acta Pharmacologica Sinica, 2020)
Motor control in the striatum is an orchestra played by various neuronal populations. Loss of harmony due to dopamine deﬁciency is considered the primary pathological cause of the symptoms of Parkinson’s disease (PD). Recent progress in experimental approaches has enabled us to examine the striatal circuitry in a much more comprehensive manner, not only reshaping our understanding of striatal functions in movement regulation but also leading to new opportunities for the development of therapeutic strategies for treating PD. In addition to dopaminergic innervation, giant aspiny cholinergic interneurons (ChIs) within the striatum have long been recognized as a critical node for balancing dopamine signaling and regulating movement. With the roles of ChIs in motor control further uncovered and more speciﬁc manipulations available, striatal ChIs and their corresponding receptors are emerging as new promising therapeutic targets for PD. This review summarizes recent progress in functional studies of striatal circuitry and discusses the translational implications of these new ﬁndings for the treatment of PD.